The Application of TSTS Learning Model to Improve Student Activity and Learning Outcomes - Magfirotul Mufida; Sholahudin Al Ayubi; Tri Novita Irawati (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2020)
This aims of the research is to increase student activity and learning outcomes througha learning model Two Stay Two Stray (TSTS). Type of research is a classroom action research (CAR). The subject of this research is 17 students of class VIII SMP Nusantara. The data collection methods are using test methods, observation, and documentation. This research was conducted in two cycles, namely cycle I and cycle II. The results of the research can be seen from indicators of the sucsess of the cycle, the first cycle of student learning activities is 72% and the second cycle is 75%. While student learning outcomes in the first cycle was 71% and the second cycle was 85%. From these indicators of sucsess, it is concluded that the application of cooperative learning model with  two stay two stray (TSTS) tipe can increase student activity and learning outcomes. Keywords: TSTS, learning activity, learning outcomes